Obstructive Sleep Apnea in Neurodegenerative Disorders: Current Evidence in Support of Benefit from Sleep Apnea Treatment - Annie C. Lajoie (Journal of Clinical Medicine, 2020)
Obstructive sleep apnea (OSA) is a prevalent disorder characterized by recurrent upper airway obstruction during sleep resulting in intermittent hypoxemia and sleep fragmentation. Research has recently increasingly focused on the impact of OSA on the brain’s structure and function, in particular as this relates to neurodegenerative diseases. This article reviews the links between OSA and neurodegenerative disease, focusing on Parkinson’s disease, including proposed pathogenic mechanisms and current knowledge on the effects of treatment.